KNOWLEDGE OF FINANCE, BOOKKEEPING & TAXATION IMPROVED THE QUALITY OF LIFE FOR THE PEOPLE - Sapta Setia Darma; Chaidir Djohar; I Ketut Wenten; Alexander Raphael (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Kedaung areas, Pamulang, South Tangerang, Banten, have a majority of the population as an entrepreneur. This area around 3 hectares with the population almost 1500 people that consist of junior high school graduated reached 85% and the majority is women. People in this areas were ensnared by loan sharks which caused by a lack of knowledge about managing finance and how to access to financial institutions, in addition the people in the community lack of understanding and skill about administration and recording or book keeping and taxation matter (especially taxes for a small business or Small Medium Enterprise), the tax is embedded in the daily activity because every citizen has the rights and obligations of taxes in the form of participating in the national development and also NPWP or taxpayer identity number is a common requirement when citizens dealing with private agencies or government institutions (with bank institution, public servant institution, etc.) Therefore this Community Service Activities (called PKM) was conducted with the participants who as entrepreneurs or others who in the Kedaung areas, Pamulang, South Tangerang, Banten. The method used in the form of requesting and collecting information from societies about existing problems and then given presentation and explanation about finance management and banking institution knowledge with an in-depth understanding of the material on how to manage to finance, access to banking institution, recording and book keeping and taxation and continued with feedback in the form of questions or input from participants and followed up by the PKM team with giving in theory or implementation. Community Service activities produced an increase in knowledge for finances and access financial institutions/banking, administrative/financial records, and taxation. The Community Service activities were expected to provide inspiration and motivation for the lecturers/researchers who would carry out the same activities, the knowledge provided could benefit the community, academics, and families.Keywords: Finance, Bookkeeping, Taxation, Kedaung Areas, Community ServiceActivities